Tracing the Single and Combined Contributions of Home-Grown Supply and Health Literacy on Fruit and Vegetable Consumption: An Empirical Exploration in Rural India - Yun-Hsuan Wu; Yun-Hsuan Wu; Spencer Moore; Cameron McRae; Cameron McRae; Laurette Dubé; Laurette Dubé (Frontiers Media S.A., 2021)
Low fruit and vegetable consumption (FVC) remains a global health challenge. Fostering subsistence agriculture through the production and home-grown consumption (HGC) of fruits and vegetables are seen as potential strategies for improving overall FVC, in particular, for developing countries like India. In addition, educational strategies targeting FVC health literacy are also used. Little evidence has documented a connection between these two strategies. We examine the single and combined influence of HGC and health literacy with regard to benefits from fruits and vegetable consumption. Data were collected from 427 rural households in the state of Odisha, India. Three outcomes were examined: FVC, as well as fruit and vegetables separately. Linear and Poisson regression were used to examine the association among home-grown consumption (HGC), FVC health literacy, and the FVC outcomes. Findings show that HGC, but not FVC health literacy, was directly associated with FVC (β = 0.65, SE = 0.10, p = 0.008) and vegetable consumption (β = 0.57, SE = 0.11, p = 0.02). However, both HGC (β = 0.58, SE = 0.05, p < 0.01) and FVC health literacy (β = −0.07, SE = 0.02, p = 0.001) were associated with fruit consumption. In addition, HGC effect is concentrated among participants who reported low FVC health literacy, especially on overall FVC and vegetables alone. Results are discussed in relation to the beneficial role played by HGC in those particularly vulnerable households who perceived little FVC health literacy. Our results provide insights on novel improved FVC consumption across all population segments. Future research should explore the complex interplay between agricultural policies and educational programs in the design of interventions promoting fruit and vegetable production and consumption.